Smartphone Use Time and Total Screen Time Among Students Aged 10–19 and the Effects on Academic Stress: A Large Longitudinal Cohort Study in Shanghai, China - Liu, Shaojie; Lan, Yukun; Chen, Bo; He, Gengsheng; Jia, Yingnan (Frontiers in Public Health, 2022)
Objective This study aimed to assess smartphone use time and total screen time among students aged 10–19 in Shanghai, China, and examine their effects on academic stress. Methods Baseline and follow-up surveys were conducted in December 2017 and December 2018, respectively, using a cohort study design with 1,771 participants. Questionnaire surveys and physical examinations of participants were conducted by trained investigators and professional school physicians, respectively. The self-administered questionnaire mainly covered demographic information, academic stress, smartphone use time, total screen time, and other lifestyle behaviors. Results The average smartphone use time of primary, middle, and high school students was 0.76 ± 0.90, 1.34 ± 1.29, and 2.39 ± 1.66 h/day, respectively; total screen time was 2.60 ± 2.63, 2.65 ± 3.39, and 3.52 ± 2.7 h/day, respectively (P < 0.001). The academic stress scores of primary, middle, and high school students were 9.25 ± 3.96, 11.97 ± 4.58, and 15.06 ± 5.10 (out of 30), respectively. The smartphone use time and total screen time were positively associated with academic stress score, with β values of 0.307 (95% CI: 0.164–0.450) and 0.171 (95% CI: 0.088–0.255), respectively. The longer the smartphone use time and total screen time, the higher the risk of abnormal academic stress, with OR values of 1.199 (95% CI: 1.103–1.303) and 1.104 (95% CI: 1.056–1.154), respectively. After stratifying by grade group, positive associations between smartphone use time or total screen time and abnormal academic stress were observed in primary and middle school students; for high school students; however, only smartphone use time had a positive association. Conclusions This study confirmed that the academic stress is widespread among students aged 10–19 in Shanghai, China. From a public health perspective, smartphone use time and total screen time should therefore be restricted for reducing academic stress and preventing related problems among adolescents in Shanghai, China, in school, family, and other environments.